To a morphogenetic type of Yantyshevsko-Juluksky fault (southern Urals) - B. G. Golionko (Известия высших учебных заведений: Геология и разведка, 2016)
The structure of the Yantyshevsko-Juluksky fault which is dividing maksut and suvanak metamorphic complexes forming Uraltau zone (Southern Urals) is examined. This fault is proved not to be an east-vergent back thrust, according to the results of investigation of mezostructural paragenezises of folds developed in the zone of dynamic influence of the southern part of the Jantushevsko- Juluksky fault. A new model proposing that this fault is a deformed thrust in which zone rocks of the suvanak complex were thrown from east to the west over metamorphic rocks of the maksut complex.